Diiodothyropropionic acid (DITPA) in the treatment of MCT8 deficiency - Verge, Charles F; Konrad, Daniel; Cohen, Michal; Di Cosmo, Caterina; Dumitrescu, Alexandra M; Marcinkowski, Teresa; Hameed, Shihab; Hamilton, Jill; Weiss, Roy E; Refetoff, Samuel (The journal of clinical endocrinology and metabolism, 2012)
Monocarboxylate transporter 8 (MCT8) is a thyroid hormone-specific cell membrane transporter. MCT8 deficiency causes severe psychomotor retardation and abnormal thyroid tests. The great majority of affected children cannot walk or talk, and all have elevated serum T(3) levels, causing peripheral tissue hypermetabolism and inability to maintain weight. Treatment with thyroid hormone is ineffective. In Mct8-deficient mice, the thyroid hormone analog, diiodothyropropionic acid (DITPA), does not require MCT8 to enter tissues and could be an effective alternative to thyroid hormone treatment in humans. The objective of the study was to evaluate the effect and efficacy of DITPA in children with MCT8 deficiency. This was a multicenter report of four affected children given DITPA on compassionate grounds for 26-40 months. Treatment was initiated at ages 8.5-25 months, beginning with a small dose of 1.8 mg, increasing to a maximal 30 mg/d (2.1-2.4 mg/kg · d), given in three divided doses. DITPA normalized the elevated serum T(3) and TSH when the dose reached 1 mg/kg · d and T(4) and rT(3) increased to the lower normal range. The following significant changes were also observed: decline in SHBG (in all subjects), heart rate (in three of four), and ferritin (in one of four). Cholesterol increased in two subjects. There was no weight loss and weight gain occurred in two. None of the treated children required a gastric feeding tube or developed seizures. No adverse effects were observed. DITPA (1-2 mg/kg · d) almost completely normalizes thyroid tests and reduces the hypermetabolism and the tendency for weight loss. The effects of earlier commencement and long-term therapy remain to be determined.